The Relationship Between Patient Safety Culture and Patient Safety Goals in the Internal Medicine Inpatient Ward at Wira Bhakti Army Hospital, Mataram - Sahat Ericson Tampubolon; Atik Kridawati; Dedy Nugroho; Ignatius Erik Sapta Yanuar (Journal of Ageing And Family, 2024)
Patient safety has been a universal reference in modern hospital practices. In Indonesia, efforts to prevent Patient Safety Incidents—such as Near Misses, Incidents, Adverse Events, and Unsafe Conditions—have been a priority in hospital safety systems. In Nusa Tenggara Barat (NTB), the incidence rate of Patient Safety Incidents is 4.8%. Army Hospital Wira Bhakti Mataram, a military hospital in NTB, plays a significant role in providing healthcare services. The hospital conducts patient safety surveys every six months to monitor and improve safety standards. This study aims to analyze the relationship between patient safety culture and patient safety incidents in the Internal Medicine Unit of Army Hospital Wira Bhakti Mataram. A quantitative analysis method with a cross-sectional approach was used. The study involved a total sample of 82 nurses, collected through in-depth interviews. The results indicate a significant relationship between patient safety culture and patient safety incidents, with a p-value of 0.003. These findings highlight the importance of fostering a strong patient safety culture to reduce incidents and improve overall healthcare quality.